Smart Nutrition Monitoring: Image-Based Allergen Detection in Pediatric Meals (International Journal of Food and Nutritional Sciences, 2022)
Food allergies in children are an increasingly significant issue in the domain of clinical nutrition and food safety, often leading to recurring illness and long-term health complications. Despite parental